Classical Comparison of Numerical Methods for Solving Differential Equations of Fractional Order - Ahmed, Mufeedah (مجلة العلوم الإنسانية والتطبيقية, 2023)
In this paper, a numerical method is presented for finding the solution of differential equations. The main objective is to find the approximate solution of fractional differential equation of order . This work is a comparison of some available numerical methods for solving linear "nonlinear" DEqs. of fractional order. However, all the previous works avoid the term of fractional derivative and handle them as a restricted variation. The present study shows that when these methods are applied to linear "nonlinear" DEqs. of fractional order, they have different convergence and approximation error.